(Th,U)O2 AND (Th,Pu)O2 FUEL UTILIZATION ON HIGH TEMPERATURE TEST REACTOR 30MWt - NURIL HIDAYATI (NIM : 10212049), ANNI
Study on various neutronic aspects of HTTR 30 MWt has been performed. HTTR or High Temperature Test Reactor with Helium as its coolant has been built in Japan and the first critical time was on November, 10th 1998. The fuel used in the calculation is UO2 or Uranium Oxide with Uranium-235 enrichment level from 3.4% to 9.9%. For the innovation, (Th,U)O2 and (Th,Pu)O2 will be used in parametric surveys. The type of fuel used is TRISO CFP or Triple-isotropic Coated Fuel Particle, that can serves as an antidote from chemical attacks and has the high-resistance proliferation characteristic. The calculation neutronic aspect includes effective multiplication factor (k-eff ) each block fuel and whole of active core, conversion ratio that show ratio between fissile material produced and fuel used, spectrumof neutrons and the power distribution of the reactor core at the beginning and at the end of the period. The design of the reactor core which is used in the calculation is 3D triangular and multi group diffusion calculation and analysis of burn-up will be calculated by using SRAC2006 code with nuclear data bases JENDL 4.0 developed by JAERI. The results shows that for UO2 enrichment fuel we can get the first criticality at 6.3% enrichment, core optimum at heterogeneous ThO2 50%-UO2 50%and homogeny core for (Th,Pu)O2 with PuO2 fraction is 6,7%. Spectrum neutron result shows that for UO2 enrichment and ThO2 50% -UO2 50% are dominant at thermal energy but for (Th,Pu)O2 is dominant at fast energy. The power distribution results show that it can be stable along operation period. Power distribution for enriched UO2 core are 2,57Watt/cm3 (BOL) and 2.39Watt/cm3 (EOL). For heterogeneous ThO2 50% -UO2 50% core is 2, Watt/cm3 (BOL and EOL). For homogeneous III (Th,Pu)O2 are 2,15Watt/cm3 (BOL) and 2,Watt/cm3 (EOL).